(untitled) (Vietnam Journal of Community Medicine, 2026)
Vernal keratoconjunctivitis is an allergic inflammatory condition of the ocular surface that can lead to vision-threatening complications and significantly impair patients’ quality of life. Currently, the search for alternative treatments to corticosteroids that possess high anti-inflammatory efficacy with fewer side effects is critical. Among these, tacrolimus, a calcineurin inhibitor, has demonstrated potent immunosuppressive capabilities. Tacrolimus in ophthalmic formulation has been proven effective in treating vernal keratoconjunctivitis and is considered safe for long-term use (1). According to the Drug Administration of Vietnam’s announcement as of December 2025, this ophthalmic formulation has not yet been officially licensed for circulation in Vietnam, whereas the dermatological ointment form is widely available. We report three cases of acute-stage VKC treated with a combination of tacrolimus 0.1% ointment (Rocimus 0.1%, The Madras Pharmaceuticals) applied to the upper eyelid skin twice daily, alongside steroids tailored to the severity of the disease. Patients were evaluated for subjective symptoms and objective clinical signs according to the Bonini classification at 1, 2, and 3 months post-treatment (2). Initial results indicate that this is a feasible method for controlling VKC: two clinical cases improved during the combination treatment period, and one case responded to treatment but subsequently relapsed upon steroid discontinuation.